2018
DOI: 10.1002/adv.21965
|View full text |Cite
|
Sign up to set email alerts
|

Xanthan Gum–Chitosan: Delayed, prolonged, and burst‐release tablets using same components in different ratio

Abstract: Chitosan and xanthan gum were combined in nine different percentages without using any cross‐linking agent. The obtained physical matrices were able to give a burst, delayed, or prolonged release of red yeast rice (RYR) on the basis of xanthan gum percentage. In fact, thermal analysis, swelling behavior, and rheological analysis pointed out that a slight interaction among xanthan gum and RYR was present. This was reflected in a burst release when the amount of xanthan gum was under the 30%. On the contrary, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
10
1
Order By: Relevance
“…Under these conditions, the entry of water will be delayed and the CL kinetics diminished. A similar delay in dissolution profiles was observed in PEC with CS as cationic polymer, with different proportions of xanthan gum or carboxymethyl starch as anionic polymers [ 8 , 33 , 35 ].…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Under these conditions, the entry of water will be delayed and the CL kinetics diminished. A similar delay in dissolution profiles was observed in PEC with CS as cationic polymer, with different proportions of xanthan gum or carboxymethyl starch as anionic polymers [ 8 , 33 , 35 ].…”
Section: Resultssupporting
confidence: 56%
“…The Korsmeyer-Peppas kinetic model ( Table 1 ) exhibits anomalous (non-Fickian) dissolution with n values close to 0.86, suggesting that the rate of water uptake into the matrix and CL release were controlled by diffusion through the hydrogel structure and swelling/erosion processes [ 16 ]. The absence of burst effects in the CS/CMC complexes justified the efficient interpenetration of CL within the network [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen in Figure 4 , CNM granules achieved the maximum percentage released of MLX at 8 h (88.77 ± 3.46%), yielding more than the reference active ingredient, the pure MLX (78.10 ± 3.01% at the same time), followed by the CFS, with 66.34 ± 2.12% and CNM + CFS with 61.86 ± 2.60% at 8 h. Different studies have shown how the improvement in drug solubility in a pH zone (6.5–7) increases drug solubility at the colon site [ 25 , 46 ]. CNM formulation had the lowest “burst effect”, thus retaining better MLX for possible enteral use.…”
Section: Resultsmentioning
confidence: 99%
“…MM, in which melting point is at 36–42 °C [ 29 ], is the major component of NLC and nanobeads. In addition, two endothermic peaks, related to the biopolymers’ dehydration for CHT at 144.4 °C [ 30 ] and for XAN at 115.0 °C [ 15 ], were noticed.…”
Section: Resultsmentioning
confidence: 99%